Strut-and-tie approach for high strength concrete deep beams - Liu, Xiu Hua. (2008)
This research is part of an on-going research programme on deep beams at Nanyang Technological University. This report mainly focuses on the mechanism of strut-and-tie model for high strength concrete deep beams. Reinforced concrete deep beams have gained considerable interest and popularity in structural engineering construction and research in recent years. Many researchers were carried out on concrete deep beams to gain an insight into the complex mechanism that governs the behaviour. The strut-and-tie model was found to be one of the most powerful methods for the design of local regions. It was also considered a useful and convenient tool for designing concrete deep beams. In the design of reinforced concrete deep beams, it is sometimes necessary to provide web openings for services or access.